The Mishnah : social perspectives - Neusner, Jacob, 1932- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1999)
The Mishnah - the second-century law code that lays the foundation, after Scripture, of normative Judaism - encompasses all subjects that pertain to the life of the Jewish nation and as such provides a systematic basis for Israel's social order and world view. Any social program has its own politics, economics, and philosophy which together define a given social entity rather than any other. And any system defining the structure of a society strives to establish a set of harmonised and coherent fundamental principles, viewpoints and attitudes in treating the components of its theory of the community. It has been long shown that the Mishnah is such a well-composed theory of world-construction. It is demonstrated here how its specific message concerning the politics and economics that define the social order recapitulate those of Aristotle. This publication has also been published in paperback, please click here for details.